PENCATATAN PERKAWINAN BEDA AGAMA DAN HAK ASASI MANUSIA DI INDONESIA - Adelia Rizky Salsabila, (2023)
Interfaith marriages are now inextricably linked to the functioning of Indonesia's multicultural society. In fact, interfaith marriages continue to occur frequently. Therefore, the purpose of this study is to examine how interfaith weddings that take place in Indonesia are protected and guaranteed by the government, as well as what potential issues there may be with documenting interfaith marriages in the future. In this regard, the author claims that in order to preserve interfaith weddings, it is important to review the Human Rights Act (UU), as well as how to record interfaith marriages in Indonesia in accordance with human rights. A qualitative research method with a statutory approach was applied in this study. Legal resources from the main, secondary, and tertiary data sources are employed. Through a review of the literature, data were gathered for this study. According to the findings of this study, interfaith marriage is one of the rights that people can pursue because, in essence, everyone has the freedom to select a spouse and start a family. The management of interfaith weddings can also be guaranteed by the state, who can also offer protection in this regard.